2020
DOI: 10.1186/s12872-020-01724-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-day and 90-day mortality among hemorrhagic and ischemic stroke patients in urban Uganda: a prospective hospital-based cohort study

Abstract: Background We report here on a prospective hospital-based cohort study that investigates predictors of 30-day and 90-day mortality and functional disability among Ugandan stroke patients. Methods Between December 2016 and March 2019, we enrolled consecutive hemorrhagic stroke and ischemic stroke patients at St Francis Hospital Nsambya, Kampala, Uganda. The primary outcome measure was mortality at 30 and 90 days. The modified Ranking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
36
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 35 publications
7
36
2
2
Order By: Relevance
“…Our results showed that intracranial hemorrhage, ischemic stroke, and unspecified subtypes had a higher risk of chronic phase mortality than subarachnoid hemorrhage. This finding is contrary to a previous study, which found that hemorrhagic stroke had a high mortality risk 26 , 31 , 32 . However, our finding may be because the number of patients in the subarachnoid hemorrhage group (the reference group) was small, and many patients with low subarachnoid hemorrhage severity were enrolled since the study was conducted on patients who survived at least two years after stroke onset.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that intracranial hemorrhage, ischemic stroke, and unspecified subtypes had a higher risk of chronic phase mortality than subarachnoid hemorrhage. This finding is contrary to a previous study, which found that hemorrhagic stroke had a high mortality risk 26 , 31 , 32 . However, our finding may be because the number of patients in the subarachnoid hemorrhage group (the reference group) was small, and many patients with low subarachnoid hemorrhage severity were enrolled since the study was conducted on patients who survived at least two years after stroke onset.…”
Section: Discussioncontrasting
confidence: 99%
“…CRP is a marker of inflammation, and its elevation in acute stroke is reportedly a poor prognostic factor [ 17 ]. GCS is widely used in assessing level of consciousness, and low levels of GCS are reportedly associated with higher mortality [ 18 ]. Lymphocytes are a subset of leukocytes, and their depletion in acute stroke is associated with poor neurologic outcome [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stroke-related mortality varies considerably between stroke types, regions, and countries ( 25 ). However, the correlates of long-term poor prognosis and death are not well characterized in the context of medullary infarction.…”
Section: Discussionmentioning
confidence: 99%